2014
DOI: 10.1002/mc.22154
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol suppresses bladder cancer tumor growth by inhibiting cell proliferation and inducing apoptosis

Abstract: The effects of the flavonoid compound, kaempferol, which is an inhibitor of cancer cell proliferation and an inducer of cell apoptosis have been shown in various cancers, including lung, pancreatic, and ovarian, but its effect has never been studied in bladder cancer. Here, we investigated the effects of kaempferol on bladder cancer using multiple in vitro cell lines and in vivo mice studies. The MTT assay results on various bladder cancer cell lines showed that kaempferol enhanced bladder cancer cell cytotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 39 publications
2
60
0
Order By: Relevance
“…Kae was reported to be an anti-tumor reagent against many cancers, such as breast cancer, pancreatic cancer, prostate cancer, and lung cancer [9-12]. Previously, we found that Kae could suppress bladder cancer by inducing apoptosis both in vitro and in vivo [13, 14]. These data highlight that this compound may be a new candidate for the prevention and treatment of bladder cancer.…”
Section: Introductionmentioning
confidence: 75%
“…Kae was reported to be an anti-tumor reagent against many cancers, such as breast cancer, pancreatic cancer, prostate cancer, and lung cancer [9-12]. Previously, we found that Kae could suppress bladder cancer by inducing apoptosis both in vitro and in vivo [13, 14]. These data highlight that this compound may be a new candidate for the prevention and treatment of bladder cancer.…”
Section: Introductionmentioning
confidence: 75%
“…Luteolin is known to promote cell death by apoptosis and preservation of normal cells and also possesses significant anticancer properties (Chen & Chen, 2013;Dang et al, 2015;Zheng et al, 2014). Its presence in honey produced by Melipona q. anthidoides and Melipona mandacaia might attribute cell protecting properties.…”
Section: Resultsmentioning
confidence: 99%
“…It promotes apoptosis of HT-29 human colon cancer cells through activating cell surface death receptors and the mitochondrial pathway (72). In a recent paper, it was revealed that kaemperol attenuates the growth of 5637 and T24 human bladder cancer cells by inhibition of the c-Met/p38 MAPK signaling pathway in vitro and in vivo (73). The antitumor activity of kaempferol also has been shown in OVCAR-3 and A2780/CP70 human ovarian cancer cell lines, it suppresses expression of VEGF and angiogenesis by inhibiting the ERK-NF-κB pathway (74).…”
Section: Flavonoidmentioning
confidence: 99%